Yemen on the brink - Boucek, Christopher; Ottaway, Marina (Carnegie Endowment for International Peace, 2010)
Yemen is facing a unique confluence of crises. A civil war in the North, a secessionist movement in the South, and a resurgence of al Qaeda are unfolding against the background of economic collapse, insufficient state capacity, and governance and corruption issues. The security challenges are the most important in the short run, because economic and governance issues cannot be addressed without a minimum of stability. This volume brings together analyses of the critical problems that have dragged Yemen close to state failure. It provides an assessment of Yemen's major security challen.